Advanced nanomaterials and their applications in renewable energy - Liu, Jingbo Louise; Sajid, Bashir (Waltham, MA : Elsevier, 2015)
Advanced Nanomaterials and Their Applications in Renewable Energy presents timely topics related to nanomaterials' feasible synthesis and characterization, and their application in the energy fields. In addition, the book provides insights and scientific discoveries in toxicity study, with information that is easily understood by a wide audience. Advanced energy materials are important in designing materials that have greater physical, electronic, and optical properties. This book emphasizes the fundamental physics and chemistry underlying the techniques used to develop solar and fuel cells with high charge densities and energy conversion efficiencies. New analytical techniques (synchronous X-ray) which probe the interactions of particles and radiation with matter are also explored, making this book an invaluable reference for practitioners and those interested in the science.
7.4 Carbon Capture and Storage7.5 Methods of CO2 Capture; 7.6 Material Used for CO2 Capture; 7.7 Summary; Author Contributions; Acknowledgments; References; Chapter 8 -- Nanosafety: Exposure, Measurement, and Toxicology; Prelog to Nanosafety and Allied Topics; 8.1 Introduction to Nanosafety; 8.2 Measurement; 8.3 Toxicology; 8.4 Summary; Acknowledgments; Author Contributions; References; Chapter 9 -- Conclusions/Postlog; Index
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed August 11, 2015).
Elsevier
Keywords: Nanostructured materials; Nanotechnology; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; Nanostructured materials; Nanotechnology; Electronic books; Electronic books